Integration of Participatory Mapping, Crowdsourcing and Geographic Information System in Flood Disaster Management (Case Study Ciledug Lor, Cirebon) - Moh. Dede; Millary Agung Widiawaty; Galuh Putri Pramulatsih; Arif Ismail; Amniar Ati; Hendro Murtianto (Journal of Information Technology and Its Utilization, 2019)
Ciledug Lor is a flood-prone area in Cirebon Regency. Flood disaster management can empower the community through participatory mapping and crowdsourcing activities. This study aims to analyze the level of floods, threats, vulnerabilities, capacities, risks and refuge locations in Ciledug Lor Village based on participatory mapping, crowdsourcing, and GIS. Various indicators of threat, vulnerability, and flood capacity are obtained from field surveys, open data and official data that have been given a value and weight which are then processed using overlay analysis to obtain flood risk parameters. Determination of refuge locations used network analysis to find out the route, distance, and effective time. The results analysis and modeling showed the average flood level in Ciledug Lor reached 2.27 meters. The refugee location for Dusun Pamosongan and Dusun Kampung Baru are to the north close to the railway tracks. Meanwhile, Dusun Karanganyar and Dusun Genggong are in the Ciledug Bus Terminal. In the future, participatory mapping, crowdsourcing, and GIS are expected to build awareness and resilience of disaster